'Keeping busy' as agency in early desistance. (February 2022) - Goodwin, Sarah
Agency in desistance research has often been understood as deliberate action undertaken in pursuit of a desisting identity. Through a micro-longitudinal approach, this research focuses on the early desistance experiences of a number of mainly White British female participants. Agency was exhibited not with a new identity in mind, but instead through 'keeping busy'. The surprising lack of identity concerns may be due to the early stages of the participants' desistance experiences, with new identities emerging later in the process. Alternatively, it may indicate a fundamental difference to the classic desistance narrative, linked to the differences between this sample and the frequently researched, Western, male, high-frequency offender. Finally, important aspects of the cultures surrounding desistance research may have shaped the narratives of desisters and the biases of researchers towards finding a concern for identity when this is not necessarily experienced in the everyday lives of desisters.